Fish Farming for Resilient Communities – Establishing the Enterprise - Nalivata, Patson; Magagula, Futhi; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Fish production has remained low in Africa and the Sub-Saharan Africa (SSA) region. Efforts have been ramped up to grow the fish industry. Aquaculture production in SSA has increased by an average of 11% annually since 2000. This is twice as fast compared with the rest of the world’s trends. Despite the momentum seen in the last decade and all the financial and technical support, SSA continues to account for less than 1% of global aquaculture production. Fish farming in South Africa is an emerging industry that consists mainly of the culture of freshwater species such as crocodiles, trout, catfish, tilapia, and ornamental fish, as well as marine species such as abalone, prawns, oysters, and mussels. In the recent past, climate variability and change have resulted in increased local temperatures that, in turn, have instigated evapotranspiration and negatively affected the breeding grounds of several essential fish species due to a reduction in the water levels of water bodies. The rise in local temperature also has influenced the physical-chemical properties of water, including temperature, pH, dissolved oxygen, salinity, and concentration of different ions in water bodies (El Morhit & Mouhir 2014). These changes negatively affect the physiological behavioral dynamics of fish as well as their natural feed resulting in lower production and productivity.